2001
DOI: 10.1128/jb.183.8.2399-2404.2001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Sieve Mechanism of Selective Release of Cytoplasmic Proteins by Osmotically Shocked Escherichia coli

Abstract: Escherichia coli cells, the outer membrane of which is permeabilized with EDTA, release a specific subset of cytoplasmic proteins upon a sudden drop in osmolarity in the surrounding medium. This subset includes EF-Tu, thioredoxin, and DnaK among other proteins, and comprises ϳ10% of the total bacterial protein content. As we demonstrate here, the same proteins are released from electroporated E. coli cells pretreated with EDTA. Although known for several decades, the phenomenon of selective release of proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 24 publications
5
70
1
Order By: Relevance
“…5 shows LpoB). The globular domain of LpoB and the rigid body of LpoA both have a diameter of ∼30 Å, allowing them to traverse the PG layer, which has ∼40-60-Å-wide pores depending on turgor (20,21). As interlayer distances have been measured only for the lateral part of the E. coli envelope, length constraints and membrane separation could be different in the leading edge of the inward growing septum, where PBP1B-LpoB predominantly localizes and acts.…”
Section: Discussionmentioning
confidence: 99%
“…5 shows LpoB). The globular domain of LpoB and the rigid body of LpoA both have a diameter of ∼30 Å, allowing them to traverse the PG layer, which has ∼40-60-Å-wide pores depending on turgor (20,21). As interlayer distances have been measured only for the lateral part of the E. coli envelope, length constraints and membrane separation could be different in the leading edge of the inward growing septum, where PBP1B-LpoB predominantly localizes and acts.…”
Section: Discussionmentioning
confidence: 99%
“…The latter molecule would have a reduced number of connected tesseras because the slightly lower level of cross-linkage is more than compensated for by the three-to fivefold longer coli has pores with a mean radius of 2.06 nm (17). In vivo, the stretched murein allows penetration of proteins with molecular masses of up to 100 kDa (17,74), indicating that larger pores with a radius of about 3 nm may exist (according to the formula given in reference 17, a globular protein with a molecular mass of 100 kDa has an estimated radius of 3.1 nm). The possible existence of larger holes indicates that the murein net is not perfect and is consistent with the data on the glycan length distribution and on the degree of cross-linkage.…”
Section: Structural Modelsmentioning
confidence: 99%
“…Because in the living cell the murein is under tension, it was roughly estimated that in vivo the stretched murein may allow free diffusion of globular proteins with a maximum molecular mass of 50 kDa. In another study it was demonstrated that EDTA treatment of E. coli cells in combination with a hyperosmotic shock released a subset of cytoplasmic proteins that were almost identical to the proteins that are able to pass through a 100-kDa-cutoff filter (74). It was speculated that this limitation was caused by the molecular sieving property of the murein sacculus that was impermeable for proteins with molecular masses of more than 100 kDa under the osmotic shock conditions.…”
mentioning
confidence: 99%
“…A genomic library was constructed in the fosmid vector pCC1FOS as previously described [35]. Total genomic DNA from cow rumen was sheared into approximately 40 kb fragments using a syringe needle, size-fractionated on a 5 to 40% linear sucrose gradient and then end-repaired to yield blunt, 5'-phosphorylated ends.…”
Section: Construction Of Cow Rumen Metagenomic Librarymentioning
confidence: 99%